Advantages and Drawbacks of Employing Full-Time (Internal) Psychologists or Part-Time (External) Psychologists - Hutchinson, Roger L.; Johnson, Raiman K. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1992)
This article relates observations about working as a full-time internal psychologist versus a part-time external psychologist in a residential treatment center. In the summary these advantages about employing external psychologists are given: (1) the external psychologist has the opportunity to function as an outside arbiter; (2) the opportunity exists for providing increased openness regarding discipline or employment concerns; (3) institutional staff may feel more comfortable making referrals to an external psychologist; (4) in-service training has the potential for being enhanced by the availability of an external psychologist's expertise; (5) the availability of an external psychologist allows in-residence, institutional caregivers the opportunity to maintain a more pragmatic, real-world oriented goal when working with students; and (6) the external psychologist has the opportunity to provide full-time staff with objective input related to the psychological well-being of students. In the summary these disadvantages of employing external psychologists are given: clients can more readily manipulate external psychologists; residents have a tendency to view external psychologists as more sympathetic to their needs; the possibility exists for a lack of a clear definition on the part of the institutional staff concerning the external psychologist's role; external psychologists may experience the frustration of being relatively ineffective in implementing changes in institutional policies; and the expectations and demands for the external/consulting psychologist to be diverse and multiply competent is potentially unrealistic. (ABL)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Consultants; Counseling Effectiveness; Counselor Role; Part Time Employment; Psychologists; Full Time Employment; Reports, General